Changes in lichen diversity and community structure with fur seal population increase on Signy Island, South Orkney Islands - Favero-Longo, Sergio E.; Cannone, Nicoletta; Worland, M. Roger; Convey, Peter; Piervittori, Rosanna; Guglielmin, Mauro (Antarctic Science, 2011)
Signy Island has experienced a dramatic increase in fur seal numbers over recent decades, which has led to the devastation of lowland terrestrial vegetation, with the eradication of moss turfs and carpets being the most prominent feature. Here we demonstrate that fur seals also affect the other major component of this region’s typical cryptogamic vegetation, the lichens, although with a lower decrease in variability and abundance than for bryophytes. Classification (UPGMA) and ordination (Principal Coordinate Analysis) of vegetation data highlight differences in composition and abundance of lichen communities between areas invaded by fur seals and contiguous areas protected from these animals. Multivariate analysis relating lichen communities to environmental parameters, including animal abundance and soil chemistry (Canonical Correspondence Analysis), suggests that fur seal trampling results in the destruction of muscicolous-terricolous lichens, including several cosmopolitan and bipolar fruticose species. In addition, animal excretion favours an increase in nitrophilous crustose species, a group which typically characterizes areas influenced by seabirds and includes several Antarctic endemics. The potential effect of such animal-driven changes in vegetation on the fragile terrestrial ecosystem (e.g. through modification of the ground surface temperature) confirms the importance of indirect environmental processes in Antarctica.